2006
DOI: 10.1007/s00066-006-1374-6
|View full text |Cite
|
Sign up to set email alerts
|

Reoxygenierung humaner koronarer glatter Muskelzellen inhibiert die HIF-1α-Genexpression und steigert die radiogene Wachstumsverzögerung und Apoptose

Abstract: Reoxygenation of coronary smooth muscle cells should be considered an option to increase efficacy of coronary brachytherapy. This could be used to reduce radiation dose and associated late side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The O 2 and OER models developed predict that the biological effectiveness of irradiated individuals with CVD can be smaller by up to 51% than the radiation dose alone implies, due to hypoxia in diseased avascular walls. An undesirable example of the oxygen effect is where radioisotopes are incorporated into intracoronary stents and the biological effect of the dose has been experimentally shown to be less than expected when treating diseased coronary arteries (Grumann et al 2006). The results determined analytically here are in agreement with the experimental studies showing underdosing by low-LET gamma-and beta-radioactive stents.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The O 2 and OER models developed predict that the biological effectiveness of irradiated individuals with CVD can be smaller by up to 51% than the radiation dose alone implies, due to hypoxia in diseased avascular walls. An undesirable example of the oxygen effect is where radioisotopes are incorporated into intracoronary stents and the biological effect of the dose has been experimentally shown to be less than expected when treating diseased coronary arteries (Grumann et al 2006). The results determined analytically here are in agreement with the experimental studies showing underdosing by low-LET gamma-and beta-radioactive stents.…”
Section: Discussionsupporting
confidence: 81%
“…Gamma emitting ( 166 Ho,192 Ir) and beta-emitting ( 32 P, 90 Sr) intracoronary stents have led to a significant reduction in restenosis (Li et al 2000). Experimental studies by Grumann et al (2006) found that restenosis may be reduced by accounting for the underdosing that can result from deploying a radioactive stent under hypoxic conditions.…”
Section: Introductionmentioning
confidence: 97%
“…Using nested PCR [15,45], Lin et al detected EBV-DNA in peripheral whole blood in 71% of NPC patients (88/124), but only in 14% of healthy volunteers (16/114) [27]. Several other groups have also reported the detection of cell-free EBV-DNA in the serum or plasma of NPC patients and healthy controls, with highly variable detection rates from 31% to 96% for NPC patients and from 0% to 14% for healthy controls [30,35,43].…”
Section: Discussionmentioning
confidence: 99%
“…Causing irreparable cellular damage triggering apoptosis is a key mechanism by which chemotherapy and ionizing radiation kill tumor cells [6,20,62]. Alterations in the expression of apoptosis-related proteins, like the inhibitor of apoptosis (IAP) protein family, however, influence the response to anti-cancer treatment.…”
Section: Introductionmentioning
confidence: 99%